2010
DOI: 10.1097/tin.0b013e3181faba64
|View full text |Cite
|
Sign up to set email alerts
|

Culinary Nutrition Camp for Adolescents Assisted by Dietetic Student Counselors

Abstract: Cook Like a Chef is a week-long, hands-on culinary nutrition program designed to encourage healthy eating behaviors among adolescents by building confidence and motivation through acquisition of cooking skills and nutrition knowledge using the guidance of a professional chef, nutrition educators, and dietetic students. This study considers the Cook Like a Chef program and evaluates its participants' increased knowledge, confidence, and motivation in healthy food choices and preparation skills. Based on the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Food skills are developed through practical experiences to perform specific tasks such as planning, selecting, and preparing foods . By encouraging such food skills, adolescents are empowered to make their own healthy meals and/or to make healthier food choices possibly including increased consumption of fruit and vegetables instead of relying on convenience foods . Furthermore, food skills have been identified as essential practical skills that young people require for independent adult life .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food skills are developed through practical experiences to perform specific tasks such as planning, selecting, and preparing foods . By encouraging such food skills, adolescents are empowered to make their own healthy meals and/or to make healthier food choices possibly including increased consumption of fruit and vegetables instead of relying on convenience foods . Furthermore, food skills have been identified as essential practical skills that young people require for independent adult life .…”
Section: Discussionmentioning
confidence: 99%
“…22,31 By encouraging such food skills, adolescents are empowered to make their own healthy meals and/or to make healthier food choices possibly including increased consumption of fruit and vegetables instead of relying on convenience foods. 31,32 Furthermore, food skills have been identified as essential practical skills that young people require for independent adult life. 33 It has been established that food and nutrition knowledge is also an important step in the process of behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…28–30,3236,38 Some of these variables have been established as precursors to changing or predicting dietary behavior in youth. For example, Bere and Klepp 39 reported that change in F/V preferences was a significant predictor of future change in F/V intake among sixth/seventh graders.…”
mentioning
confidence: 99%
“…In the intervention literature, published accounts of youth nutrition programs with cooking components are limited and vary in the degree of hands-on cooking permitted and ages targeted. [28][29][30][31][32][33][34][35][36][37] Nearly all in-school interventions target elementary school students (5-to 11-year-olds) while middle school programs (sixth-eighth grade: 11-to 14-year-olds) take place in camps and afterschool settings, limiting the consistency in attendance that a classroom-based program affords. While not delivered in middle school classrooms, 3 programs with cooking components measured change in consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation